Viologen cyclophanes: redox controlled host–guest interactions. Issue 87 (10th September 2015) - Berville, Mathilde; Karmazin, Lydia; Wytko, Jennifer A.; Weiss, Jean
Abstract : Bis(viologen) cyclophanes with alkyl linkers demonstrate redox-dependent host–guest properties, including the formation of a crystalline mixed valence species. Abstract : Viologens can exist in three redox states varying from dicationic to neutral. This work emphasizes the control of the host–guest properties in bis-viologen cyclophanes. Two flexible cyclophanes were prepared by a cyclisation method sensitive to the odd/even number of carbons in the flexible chains linking two viologens. C5 and C7 cyclophanes were characterised by X-ray diffraction in their tetracationic state and their diradical dicationic state. In the presence of tetrathiafulvalene or methyl viologen as guests, inclusion complexes were obtained, including a mixed valence species.